Evaluasi Yuridis terhadap Implementasi Mekanisme Perlindungan Justice Collaborator dalam Praktik Peradilan Pidana di Indonesia - Nuna, Riknan; Thalib, Satriyo Pratama; Moonti, Roy Marthen; Kasim, Muslim A. (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The protection of justice collaborators (JC) is a vital element in the eradication of extraordinary crimes such as corruption, narcotics, and premeditated murder. However, in the practice of criminal justice in Indonesia, there is still a gap between the normative legal framework and the implementation of protection for JCs. This research aims to juridically evaluate the effectiveness of the JC protection mechanism based on national regulations and judicial practice. The method used is normative legal research with a case study approach, through analysis of legislation, court decisions, and LPSK documents. The results of the study show that weak institutional coordination, inconsistency of decisions, and lack of post-trial protection are the main obstacles. It is necessary to codify JC protection in criminal procedure law and strengthen the capacity of legal apparatus to realize comprehensive protection. This research contributes to the development of a fairer and more responsive justice system in protecting the moral courage of JCs.